2020
DOI: 10.1371/journal.pone.0231941
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory deficits after vincristine-induced lesions to the dorsal hippocampus

Abstract: Vincristine is a commonly used cytostatic drug for the treatment of leukemia, neuroblastoma and lung cancer, which is known to have neurotoxic properties. The aim of this study was to assess the effects of vincristine, injected directly into the dorsal hippocampus, in spatial memory using the spatial cone field discrimination task. Long Evans rats were trained in the cone field, and after reaching training criterion received bilateral vincristine infusions into the dorsal hippocampus. Vincristine-treated anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Further assays revealed that cytotoxicity was mediated by depolarization of the mitochondrial membrane potential after 48 h of exposure to chemotherapeutics [6] . Other studies have shown that another chemotherapeutic drug, vincristine, destroys hippocampal tissue when administered unilaterally or bilaterally to mice [60] .…”
Section: Resultsmentioning
confidence: 98%
“…Further assays revealed that cytotoxicity was mediated by depolarization of the mitochondrial membrane potential after 48 h of exposure to chemotherapeutics [6] . Other studies have shown that another chemotherapeutic drug, vincristine, destroys hippocampal tissue when administered unilaterally or bilaterally to mice [60] .…”
Section: Resultsmentioning
confidence: 98%
“…In particular, the vHip governs the overall affective state and moderates the effects of emotional experience and stress. The dHip, instead, is mainly involved in controlling cognitive functions, including memory, learning and spatial contextual detection [ 68 , 69 , 70 ]. In addition, both subregions are involved in delaying meal initiation and influencing the amount of food consumed [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another type of neurological side effect of chemotherapeutics such as vincristine involves cognitive and memory deficits commonly referred to as chemo brain [ 4 6 ]. This suggests that central as well as peripheral neurons can be negatively affected by chemotherapy.…”
Section: Introductionmentioning
confidence: 99%